Environmental filtering and dispersal limitation jointly shape the taxonomic, functional and phylogenetic diversity in a subtropical karst forest of China - Long, Qingzhi; Zhan, Zhili; Du, Hu; Peng, Wanxia; Su, Liang; Zhang, Hao; Zeng, Zhaoxia; Zeng, Fuping; Tan, Weining; Mo, Youwang; Deng, Xichao; Xie, Yanjun; et al. (Frontiers in Plant Science, 2025)
IntroductionCommunity assembly involves species forming communities through interactions and environmental adaptation, with traits and phylogeny playing key roles. Analyzing these factors is crucial for understanding community assembly and improving ecological restoration and biodiversity conservation, especially in karst ecosystems, where research is limited.MethodsHere, we evaluated six metrics of taxonomic, phylogenetic and functional diversity in a subtropical climax forest, and then derived the relative contribution of environmental and spatial conditions on the diversity metrics.ResultsThe results indicated that, except for the mean pairwise distance (MPD) index, all other indices exhibited a higher spatial distribution pattern on slopes compared to depressions. The MPD index, however, displayed a more homogeneous pattern, with no significant differences observed across terrains. Our findings suggest that topography has a stronger and more consistent influence on species, functional, and phylogenetic diversity than soil factors. Among these, phylogenetic diversity showed the most pronounced response to topographic variation (especially elevation, slope, and terrain wetness index), indicating that evolutionary lineage distribution is more sensitive to terrain changes than functional or species diversity. In addition, species diversity was most affected by dispersal limitation among the three types of diversity, suggesting that significant spatial variation in community composition is largely constrained by the dispersal ability of species. In contrast, phylogenetic diversity was most affected by environmental filtering, highlighting the strong selective effect of environmental conditions on community phylogeny. Functional diversity, on the other hand, showed a smaller degree of response to both filtering and dispersal, with dispersal limitation having a higher impact than environmental filtering.DiscussionThis study reveals the spatial pattern of karst plant diversity in southwest China and its influencing factors, as well as the mechanism of community construction, providing a theoretical foundation and scientific basis for biodiversity conservation and vegetation restoration in karst areas.